Mapping Western Balkans Civilian Capacities for Peace Operations - Karlsrud, John; Milošević, Marko (Journal of Regional Security, 2018)
Over the past several years the United Nations has increasingly emphasized the role that civilian capacities can play in post-conflict peacebuilding and called for member states to provide expertise. This special issue of the Journal of Regional Security will explore the civilian capacities of the Western Balkans countries and whether there is political will to respond to the call to deploy civilian capacities to UN peace operations and other international organizations. Looking at how Western Balkan countries train, roster and deploy civilian capacities, it will also explore whether increased cooperation in this area could be considered as a security community practice, nurturing bilateral relations and building cooperation in the Western Balkan region. The article finds that there is still a great gap between the expressed policy intent of providing civilian capacities to peace support operations, and putting it into practice. There is also lack of a strategic consideration of how the training and deployment of civilian capacities to peace operations could build legitimacy in international organizations and enhance regional cooperation among the states in the Western Balkans. The article recommends the initiation of a regional dialogue on training and rostering of civilian capacities, realizing synergies and furthering regional cooperation.